NAT1 and NAT2 genetic polymorphisms and environmental exposure as risk factors for oesophageal squamous cell carcinoma: a case-control study. Issue 1 (December 2015) - Matejcic, Marco; Vogelsang, Matjaz; Wang, Yabing; Parker, Iqbal
Abstract Background Tobacco smoking and red meat consumption are some of the known risk factors associated with the development of oesophageal cancer. N-acetytransferases (NAT1 andNAT2 ) play a key role in metabolism of carcinogenic arylamines present in tobacco smoke and overcooked red meat. We hypothesized thatNAT1 andNAT2 genetic polymorphisms may influence the risk of oesophageal cancer upon exposure to environmental carcinogens. Methods Single nucleotide polymorphisms (SNPs) in theNAT1 andNAT2 genes were investigated by genotyping 732 cases and 768 healthy individuals from two South African populations to deduce the acetylator phenotype (slow, intermediate or rapid) from the combination of the genotyped SNPs. Results The 341 CC genotype (rs1801280) was significantly associated with a reduced risk for oesophageal cancer in the Mixed Ancestry population (OR = 0.31; 95% CI 0.11-0.87). TheNAT2 slow/intermediate acetylator status significantly increased the risk among cigarette smokers in the Black population (OR = 2.76; 95% CI 1.69-4.52), as well as among alcohol drinkers in the Mixed Ancestry population (OR = 2.77; 95% CI 1.38-5.58). Similarly, theNAT1 slow/intermediate acetylator status was a risk factor for tobacco smokers in the Black population (OR = 3.41; 95% CI 1.95-5.96) and for alcohol drinkers in the Mixed Ancestry population (OR = 3.41; 95% CI 1.70-6.81). In a case-only analysis, frequent red meat consumption was associated with a significantly increased cancer risk forNAT2 slow/intermediate acetylators in the Mixed Ancestry population (OR = 3.55; 95% CI 1.29-9.82; P = 0.019), whereas daily white meat intake was associated with an increased risk amongNAT1 slow/intermediate acetylators in the Black population (OR = 1.82; 95% CI 1.09-3.04;P = 0.023). Conclusions Our findings indicate that N-acetylation polymorphisms may modify the association between environmental risk factors and oesophageal cancer risk and that N-acetyltransferases may play a key role in detoxification of carcinogens. Prevention strategies in lifestyle and dietary habits may reduce the incidence of oesophageal cancer in high-risk populations.